Serum Ferritin Independently Predicts the Incidence of Chronic Kidney Disease in Patients with Type 2 Diabetes Mellitus - Wu, Yun Hong (Diabetes Metab Syndr Obes, 2020)
AIM: This study aimed to determine whether serum ferritin (SF) is an independent risk factor of the incidence of chronic kidney disease (CKD) and rapid renal function decline (RFD) in male Tibetan patients with type 2 diabetes mellitus (T2DM). METHODS: We performed a retrospective cohort study that included 191 male Tibetan patients with T2DM without CKD. Patients were divided into three groups according to the level of SF. The following outcomes were measured: cumulative incidence of chronic kidney disease [i.e. estimated glomerular filtration rate (eGFR) <60 mL/min per 1.73 m(2) and/or urinary albumin/creatine ratio (ACR) ≥30 mg/g] and RFD (i.e. decrease in eGFR of ≥25% from baseline or a decline rate of ≥3 mL/min per 1.73 m(2) annually). RESULTS: In total, over a median follow-up period of 23 months, 30 (15.7%) and 89 patients (46.6%) developed CKD and RFD. In multivariable Cox models, a 100 ng/mL increment in SF was associated with a 1.12-fold (95% CI: 1.02–1.24) higher adjusted risk for incidence of CKD. The adjusted-HR of CKD was 1.31 (95% CI: 0.38–4.53) and 2.92 (95% CI: 0.87–9.77) for those in tertile 2 and tertile 3, respectively, compared with the patients in tertile 1. However, SF was not significantly associated with RFD (adjusted-HR: 1.06, 95% CI: 0.99–1.14). CONCLUSION: Serum ferritin independently predicts the incidence of CKD in male Tibetan patients with T2DM. High levels of serum ferritin may play a role in the pathogenesis leading to the development of CKD in T2DM.